Cash confident an entrepreneur's guide to creating a profitable business - Houston, Melissa (Ascent Audio, 2023)
It's time for you to own your financial power and learn to make smarter, and more profitable, business decisions. Let's start with a question ... Do you know why 82 percent of new businesses fail? Poor money management. To focus on profit and wealth building, entrepreneurs need to become confident about understanding their business finances as well as their ability to manage them. Everything in business affects your bottom line, as do all your decisions. You need to take ultimate responsibility for the financial future of your business-you need to become cash confident! Cash Confident is a roadmap to becoming a financially savvy business owner. It will take you through the no-nonsense 5-Step Cash Confident Framework and unpack money management 101 in clear, easy-to-follow steps to prime you for success. In this book, you'll learn: how to think about money in your business; how to create a financial plan for your business; how to set up a money advisory board; how to beat CEO imposter syndrome; how to recognize your business's financial strengths and weaknesses; and how to put profit ahead of all else.